Experimental investigation on the bond performance of sea sand coral concrete with FRP bar reinforcement for marine environments. Issue 3 (February 2023) - Sun, Li; Wang, Cha; Zhang, Chunwei; Yang, Zeyu; Li, Chuang; Qiao, Pizhong
The world is rich in marine resources, and the use of seawater, sea sand and coral instead of fresh water, river sand and gravel can solve problems such as the scarcity of traditional materials for marine engineering construction. Additionally, fibre-reinforced polymer (FRP) bars have demonstrated excellent corrosion resistance performance, which can effectively solve the problem of the corrosion of steel in harsh marine environments. To study the bond performance between FRP bars and sea sand coral concrete (SSCC), 72 specimens of direct Pull-out were designed, and relevant tests were carried out to explore the effects of fibre types, bar diameters, bond lengths and SSCC strength grades. The results show that the bond strength between carbon fibre-reinforced polymer (CFRP) bars and SSCC was higher than that of basalt fibre-reinforced polymer (BFRP) bars and glass fibre-reinforced polymer (GFRP) bars. The splitting damage pattern occurred in most of the specimens; the bond strength between FRP bars and SSCC decreased with increasing diameter and bond length of FRP bars but increased with increasing SSCC strength grade. As a result, by fitting the bond-slip curves obtained from the tests, the bond-slip constitutive relationship between FRP bars and SSCC specimens was obtained, which clearly and precisely represents the bond failure process of SSCC with FRP bar reinforcement.